2019
DOI: 10.1101/681445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Damage-related changes in the cerebellum of juvenileOncorhynchus masou: reactivation of neurogenic niches and astrocytic response

Abstract: 10In the cerebellum of juvenile Oncorhynchus masou, proliferating BrdU+ and HuCD+ cells and 11 constitutive neurogenic niches were detected in different zones; the largest number of labeled 12 cells were found in the dorsal part of the molecular layer and the dorsal matrix zone (DMZ). 13Cells labeled with glutamine synthetase (GS) and radial glia were also present in the intact O. 14 masou cerebellum. The most intensive proliferation was detected in the rostral part of 15 cerebellum. This part is assumed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
(117 reference statements)
1
6
0
Order By: Relevance
“…Studies on medaka brain have also shown that in optic tectum, as a part of proliferative populations, aNSCs are actually neuroepithelial-like stem/progenitor cells and are not radial glial cells [4]. Similar results were obtained in other studies on fish brain, in particular, optic tectum [16], mesencephalic tegmentum [14], and cerebellum [13,17].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Studies on medaka brain have also shown that in optic tectum, as a part of proliferative populations, aNSCs are actually neuroepithelial-like stem/progenitor cells and are not radial glial cells [4]. Similar results were obtained in other studies on fish brain, in particular, optic tectum [16], mesencephalic tegmentum [14], and cerebellum [13,17].…”
Section: Introductionsupporting
confidence: 80%
“…The brain of an adult fish is a site of continuous intense proliferative activity, not limited only to the telencephalon [12]. In some areas of proliferation in the brain, tissue-specific stem cells have a neuroepithelial phenotype rather than radial glial characteristics [5,13]. Studies on juvenile salmon fish showed that in the cerebellum of O. masou [13] and in the mesencephalic tegmentum of the chum salmon Oncorhynchus keta [14], most aNSCs have a neuroepithelial phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the PCNA localization in the cerebellum of O. masou showed that the patterns of constitutive proliferation were local, small in size, CNNs located in the area of the DMZ, as well as in the molecular layer of all neuroanatomical zones [ 68 ]. The patterns of neurogenesis, revealed using the protein marker of neuronal differentiation HuCD, showed that in intact juveniles the HuCD+ cells are localized within the CNNs of the neuroepithelial type [ 13 ]. According to the data obtained on mammals, a high CBS concentration is necessary for the early maturation and growth of neuronal networks, which indicates the involvement of H 2 S in neuronal differentiation [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their ontogenesis is characterized by such phenomena as developmental delay and retention of signs of the embryonic organization of CNS which occur at the stage of active brain growth, where the morphogenesis processes are most clearly and fully expressed [ 11 ]. This feature of salmon CNS development, referred to as embrionalization, is confirmed by the presence of a large number of embryonic neuronal stem cells (NSCs) corresponding to cells of the neuroepithelial (NE) type, as well as radial glial (RG) cells corresponding to adult progenitors [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%